Desarrollo de una propuesta para un sistema de tratamiento del agua residual de la empresa de Lácteos IBEL (2019)
With the respective literature review, pollutant removal methods were studied to be evaluated at the experimental level to choose the optimal reagents and processes. To comply with the regulations, six processes were proposed: grease trap, oxidation, neutralization, coagulation, flocculation and filtration, obtaining favorable results to comply with the dumping regulations. According to the theories and design principles, the industrial staggering of the established equipment was carried out taking into account the company's specifications and experimentally evaluated. Finally, the viability of the project was evaluated taking into account investment, operation and net income costs of the company through a B/C indicator, likewise the study of possible fines was made if the Ministerio de Ambiente y Desarrollo Sostenible.